Community Based Analysis of the Development of the Lasiana Beach Tourism Area - Messakh, Faldo Stivan; Pandie, David B. W; Fanggidae, Apriana H.J. (Journal of Social Research, 2023)
This research endeavors to conduct a comprehensive analysis of the Community-Based Development of the Lasiana Beach Tourism Area. Employing a qualitative descriptive approach, data for this study were gathered through interviews, observation, and documentation. The research's focal points include Attractions, Accommodation, Accessibility, Awareness/Promotion, and Amenities/Supporting Facilities. The findings reveal that the development of the Lasiana Beach tourist area has yet to achieve its intended goals, and its progress has not been optimal, primarily due to the absence of diverse arts and cultural events as attractions. The inadequate provision of accommodations such as homestays, cafes, and restaurants within the vicinity further hinders the area's development. However, commendably, the road accessibility is excellent. There exists a noticeable deficiency in promotional efforts, particularly through digital and non-digital media channels and events. Additionally, the absence of supporting facilities within the area diminishes its appeal to potential tourists. This inadequacy is largely attributed to the community's limited involvement in the development of the Lasiana Beach area. To realize the full potential of Lasiana Beach as a tourist destination, it is imperative for the community to actively participate in its development. Collaborative efforts can enhance the range of attractions, improve accommodations, intensify promotional strategies, and bolster supporting facilities, ultimately fostering sustainable tourism growth in the region.